Correlation of Financial Innovation, Stock Market, Cryptocurrency on Economic Growth - Waluyo Jati; Rachmawaty Rachmawaty; Holiawati Holiawati; Iman Syatoto (Economics Development Analysis Journal, 2022)
Indonesia has had the critical issue of economic growth in the last ten years which the trend of economic growth was declining year by year, in 2011 GDP growth YoY was 6.5% then declined become 5% in 2019 (before Covid-19 pandemic) and worst in Pandemic Era become -5.3%. This research aims to provide an understanding of the effect of short term and long term of Financial Innovation, Stock Market and Cryptocurrency on Indonesia's economic growth using the Vector Error Correction Model (VECM) method. The methode was chosen based on Stationary Analysis and Cointegration Test. It is shown that the data was non-Stationary and the result of Cointegration Test there was a conintegration at 0.05 level. Enrich with the analysis in Impulse Response and Variance Decomposition to obtain the fluctuated economic growth impacted by those variables on a monthly basis, which previous researchers have not researched. The results showed that the correlation of the Stock Market, Financial Innovation and Cryptocurrency to Indonesia's economic growth, in the long run, all the variables give a positive correlation. Still, in the short-run, only the stock market and economic growth give a positive correlation. The result of the long and short run of VECM is supported by Impulse response and variance decomposition that stock market has the most significant impact to economic growth